Soil Development as a Function of Time in the Rouge River Basin, South-Central Ontario - Mahaney, William; Sanmugadas, Kalmia (Géographie physique et Quaternaire, 1986)
ABSTRACTThree soils of postglacial age, representing a chronosequence in the Rouge River Basin of south-central Ontario, were studied to determine variations in morphological, physical, chemical, and mineralogical properties. These soils, forming in alluvium of mixed mineralogy represent the Late HoIocene (Entisol), Middle Holocene (lnceptisol),and Early Holocene (lnceptisol) surfaces. Horizon differentiation and soil thickness increase with greater age, while pH drops slightly in the sola of the older profiles. Cation exchange capacity (CEC) and organic matter in the surface horizons increases slightly with age, while, for the most part, CaCO3 and Ca/ Mg ratio decrease. Significant changes occur over time, especially with an increase of dithionite-extractable iron with age (from ~ 0.20 in the Late Holocene soil to ~ 0.70 in the Middle to Early Holocene profiles). Illite and illite-smectite tend to decrease with age, being replaced by small amounts of chlorite and vermiculite. In spite of some variability in parent materials due to stratification and preweathering, and minor changes in species composition, the changes in soil properties are attributed to processes of soil formation acting over time.